Electro-Modulation of Tubulin Properties and Function - Chafai, Djamel Eddine; Cifra, Michal (Methods in molecular biology, 2022)
Microtubules composed of tubulin heterodimers represent highly dynamic structures. These structures are essential for basic cellular functions, such as cell division. Microtubules can grow or shrink in response to environmental signals, principally chemical cues. Here, we provide an alternative-physical-strategy to modulate tubulin properties and its self-assembly process. The conformation and electrical properties of tubulin subunits are modulated by nanosecond electropulse signals. The formed structures of electrically treated tubulin are tightly linked to the degree of conformational and electrical properties changes induced by nanosecond electropulses. This strategy opens a new way for controlling the self-assembly process in biomolecules as well as in bioinspired materials.
Keywords: Tubulin; elektřina; kvarterní struktura proteinů; Microtubules; tubulin; mikrotubuly; Protein Structure, Quaternary; Electricity